A bilevel interactive energy trading method for distribution networks incorporating multiple microgrids - LIN Da; CHEN Zhe; LI Zhihao; WANG Xiangjin; TANG Yajie; QIN Jiakai (Zhejiang dianli, 2025)
To enhance the operating revenue of distribution networks and microgrids while reducing microgrid energy usage costs， this paper proposes a distributed trading strategy for microgrids based on Stackelberg game theory. First， a multi-objective bilevel optimization trading model for distribution networks and microgrids is established based on Stackelberg game theory. In this framework， the upper level models the distribution network trading scheme， with the objective of maximizing the agent’s profit； the lower level formulates the microgrid energy usage optimization model， aiming to minimize the operator’s operational costs. Subsequently， the Karush-Kuhn-Tucker （KKT） conditions are introduced to convert the bilevel model into a single-level formulation. Through linearization techniques， the reformulated model is further transformed into a mixed-integer linear programming （MILP） model， thereby resolving the nested solving challenges inherent in hierarchical transaction models. Simulation results demonstrate that the proposed strategy significantly increases the distribution network agent’s revenue and reduces microgrid operational costs. This work provides a reference for decision-making in electricity markets incorporating microgrids.